Deterministic Transfer of Large-Scale β-Phase Arsenic on Fiber End Cap for Near-Infrared Ultrafast Pulse Generation - Yu, Qiang; Chen, Cheng; Guo, Kun; Deng, Haiqin; Yi, Tianan; Zhang, Yan; Su, Wei; Wu, Jian; Zhang, Kai (Frontiers in Materials, 2021)
Gray arsenic (β-phase) has aroused great attention in photonics and electronics applications, as a novel family member of two-dimensional (2D) elemental crystals of group-VA. Here, β-phase arsenic (β-As) bulk crystals were synthesized via the chemical vapor transport (CVT) method. Meanwhile, large scale β-As nanoflake was transformed using polydimethylsiloxane (PDMS) assisted dry transfer method, and was placed on the end cap of optical fiber with high coverage over the core area. Moreover, the β-As was used as saturable absorber in ytterbium-doped fiber ring cavity resonance, and we demonstrated near infrared ultrafast pulse fiber laser with the central wavelength, repetition rate and signal-to-noise ratio (SNR) of 1037.3 nm, 0.6 MHz and 67.7 dB, respectively. This research demonstrated a 2D material small area deterministic transfer method, and promotes the potential application of group-VA crystals in near infrared ultrafast laser generation.